Is the Transcranial Magnetic Stimulation an Adjunctive Treatment in Fibromyalgia Patients? - YAĞCI, İLKER (AVES, 2014)
Objective: To investigate the effectiveness of low-frequency (LF) repetitive transcranial magnetic stimulation (rTMS) to the motor cortex area in fibromyalgia patients who are resistant to medical treatment. Material and Methods: A total of 25 patients were randomly assigned to the study, who were in the active rTMS (n=13) or sham stimulation (n=12) group. For the rTMS group, the main stimulation parameters were 90% of motor threshold for 60 seconds at 1 Hz and a 45-second interval between each train. Ten sessions of low-frequency rTMS, which had a total of 1200 pulses at each session, were applied to the left primary motor cortex area daily over a period of 2 weeks. For the sham group, the same parabolic coil was placed at 90 degrees angles to the motor cortex area, and the patients received 10 sessions of sham stimulation. The outcome parameters were pain intensity, which was measured by visual analog scale (VAS), Fibromyalgia Impact Questionnaire (FIQ), and the Beck Depression Inventory (BDI). Results: A significant improvement in pain intensity, FIQ, and BDI scores was seen at the 10th day and first and third months in both groups. Although the mean of parameters of the rTMS groups was better than the sham group, the difference did not reach statistical significance, except FIQ scores at the 10th day in the real rTMS group. Conclusion: Patients with fibromyalgia who enroll in real TMS did not present significant differences in long-term follow-ups with respect to those who enrolled in the sham TMS group.
Keywords: Fibromyalgia; transcranial magnetic stimulation; pain; MOTOR CORTEX; PAIN; RTMS; DIAGNOSIS; NEUROLOGY